Analisis Fasilitas Dan Promosi Media Sosial Video Youtube Terhadap Minat Kunjungan Ulang Objek Wisata Alam di Kabupaten Merangin - Fenisi Resty; Kelik Purwanto; Alex Ferdinal; Sujito Sujito; Chintia Lestari (CV. Ulil Albab Corp, 2025)
Lake Pauh is a volcanic lake formed by volcanic activity millions of years ago. Lake Pauh is a very beautiful area and is a tourist attraction in Merangin Regency. Danau Pauh has problems with facilities such as playgrounds and speed boats. And also experiencing problems with social media promotion which is not yet optimally known to outsiders. This research was conducted to determine the effect of social media facilities and YouTube video promotions on interest in revisiting natural tourist objects in Merangin district. The purpose of this research was to find out and analyze YouTube video social media facilities and promotions for interest in repeat visits. This study used a quantitative method with data collection using a questionnaire. Data Analysis Techniques with Validity Test, Reliability Test, Multiple Linear Regression Analysis, Classical Adjudication Test, T Test, F Test, Determination Test (R2). The population in this study were 14,092 respondents and 389 samples were used as samples.The results showed that partially (t test) it was proven that facilities had a significant effect on repeat visit intentions, and social media promotion of YouTube videos had a significant effect on repeat visit intentions. As well as simultaneously (test f) social media facilities and promotions have a significant effect on intention to return visits. Adjusted R2 value obtained a coefficient value of 0.608. Which means all the independent variables can affect 60.8 on the dependent variable. While the remaining 37.6% can be influenced by other factors not tested in this study.